Strategi Komunikasi BKKBN Kabupaten Maros Dalam Menciptakan Selt- Disclosure (Keterbukaan Diri) Masyarakat Pasangan Usia Subur (PUS) Dalam Program Penyuluhan Berbasis Konseling Di Di Tompobulu, Maros, Sulawesi Selatan - Habib, Habib; Ri’aeni, Ida (AGUNA: Jurnal Ilmu Komunikasi, 2025)
Abstract . This research aims to analyze the factors that influence the PUS community to tend to cover themselves in counseling-based outreach in Tompobulu Village. The type of research used is a qualitative research method, the data obtained is from the results of observations and research interviews from all specified informants. The results of the research show that the factors that influence the EFA Community to cover themselves in the extension agenda are (1) shame, (2) assumptions that are sensitive to family planning programs, and (3) the quality of some instructors who are considered to still not embrace the EFA Community so that comfortable and safe to show self-disclosure. Meanwhile, the appropriate communication strategy in counseling-based outreach to PUS is a communication strategy with a Social Construction perspective. Starting with changing the PUS community's view of the family planning program first, then carrying out various strategies for reconstructing the meaning of family planning programs, and ending with creating a new meaning, as well as feeling confident for the PUS community to want to open up and be actively involved in the education-based agenda. counseling. Keywords: Communication Strategy, Self-Disclosure, Couples of Reproductive Age/ Couples of Childbearing Age